2015
DOI: 10.1128/aac.04305-14
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Treatment Causes a Decrease in Fibrinogen Levels

Abstract: The objective of this study was to assess the impact of tigecycline treatment on coagulation parameters, specifically fibrinogen, in patients with severe infections. We examined 20 cases of tigecycline-treated patients with severe infections, including hospitalacquired pneumonia, complicated intra-abdominal infections, complicated skin and soft tissue infections, and bloodstream infections. We monitored the relative markers of coagulation and renal and liver function before, during, and after treatment. Fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 15 publications
2
58
0
Order By: Relevance
“…One could hypothesize that high-dose treatment with tigecycline is a possible risk factor for hypofibrinogenemia which is supported by the observations of Routsi et al who found high doses of this drug leading to hypofibrinogenemia [4]. Moreover, Zhang et al described a dose dependent decrease of fibrinogen levels [5].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…One could hypothesize that high-dose treatment with tigecycline is a possible risk factor for hypofibrinogenemia which is supported by the observations of Routsi et al who found high doses of this drug leading to hypofibrinogenemia [4]. Moreover, Zhang et al described a dose dependent decrease of fibrinogen levels [5].…”
Section: Discussionmentioning
confidence: 81%
“…A described side effect during tigecycline therapy is coagulopathy. Three small-scale studies reported effects of tigecycline on coagulation [3][4][5]. A clinical trial observed decreased fibrinogen levels as assessed by the classical Clauss method during high-dose treatment with tigecycline in a group of 45 intensive care patients [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest tolerated dose was 200 mg per day (Muralidharan et al, 2005). However, a recent study showed that high doses of tigecycline are associated with decreased fibrinogen level along with prolonged prothrombin time, activated partial thromboplastin time, and thrombin time (Zhang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…A review of the adverse event profile of TGC suggested that off-label use rarely causes unexpected adverse events, presumably due to usage with extreme caution. Nevertheless, more recently, the use of TGC has been associated with decreased fibrinogen levels, especially at high doses [9]. …”
Section: Introductionmentioning
confidence: 99%